Spaceborne Reflector SAR Systems with Digital Beamforming - Huber, Sigurd; Younis, Marwan; Patyuchenko, Anton; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Aerospace and Electronic Systems, 2012)
Spaceborne synthetic aperture radar (SAR) imaging enters an era where increasingly short revisit times, or large swath widths, respectively, and high spatial resolutions are requested. These requirements impose contradicting constraints on conventional SAR systems using analog beamforming technology. The development for future radar satellites is therefore towards digital beamforming (DBF) systems where the analogous receiver hardware is replaced by digital components. Concerning the SAR antenna the innovative concept of a parabolic mesh reflector in conjunction with a digital feed array is becoming a promising architecture for this new SAR system generation. These antennas, already a mature technique for communication satellites, have the potential to outperform planar array antennas in terms of gain at a moderate hardware effort. This article provides a hardware concept study based on a design in X-band. Focus is put on DBF algorithms adopted to the SAR case and important performance figures are derived. © 2011 IEEE.
DLR Import::2019-04-02